Distribution and bio-ecological characteristics of the species Meloe Tuccius Rossi, 1792 (Meloidae: Meloe Linnaeus, 1758) in the Tashkent Region - Kalbayeva Sarigul Iqlas qizi (Scientific Trends, 2025)
This article presents the distribution and bio-ecological characteristics of the species Meloe tuccius Rossi, 1792, belonging to the genus Meloe Linnaeus, 1758, distributed in the regions of Tashkent region. In particular, information is provided about the development of the larval stages, imago phase, and bio-morphological structures of the species Meloe tuccius Rossi, 1792. As a result of the research, the bio-ecological characteristics and practical significance of the species Meloe tuccius Rossi, 1792 were studied. General conclusions were given regarding the identified species.
Keywords: Blister beetle, Meloe tuccius species, area, Tashkent region, entomophagous, pest, larva, imago